2020
DOI: 10.1097/md.0000000000023317
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexmedetomidine-propofol and ketamine-propofol administration during sedation-guided upper gastrointestinal system endoscopy

Abstract: Background: Dexmedetomidine and ketamine popular sedative agents that result in minimal respiratory depression and the presence of analgesic activity. We aimed to compare the effectiveness and safety of a dexmedetomidine-propofol combination and a ketamine-propofol combination during upper gastrointestinal system endoscopy. Methods: The study commenced after receiving approval from the local ethics committee. Patients between 18 and 60 years in the American Society of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Our findings revealed that esketamine had quicker onset than dexmedetomidine. The respective onset time was 12 (95% CI, 10.25–14) min in Group D and 2 (95% CI, 2–3) min in Group K, which was consistent with Pees’ ( Pees et al, 2003 ) and Tekeli’s research ( Tekeli et al, 2020 ). Our difference from Pee’s research ( Pees et al, 2003 ) was the subjects were adults in Pee’s but children in ours.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings revealed that esketamine had quicker onset than dexmedetomidine. The respective onset time was 12 (95% CI, 10.25–14) min in Group D and 2 (95% CI, 2–3) min in Group K, which was consistent with Pees’ ( Pees et al, 2003 ) and Tekeli’s research ( Tekeli et al, 2020 ). Our difference from Pee’s research ( Pees et al, 2003 ) was the subjects were adults in Pee’s but children in ours.…”
Section: Discussionsupporting
confidence: 88%
“…The 0.5 mg.kg −1 of ketamine can increase the BIS value but not 0.2 mg.kg −1 . In adults receiving gastroscopy, it has also been shown that the BIS value in patients receiving propofol combined with ketamine was significantly higher than that in patients receiving propofol combined with dexmedetomidine (Tekeli, et al, [ 21 ]). Similar results were also obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The BIS value was 85-100 normally, 65-85 for a sedated state, 45-65 for an anesthetic state, and below 40 for a burst suppression state [9,10]. Moreover, relevant studies have shown that following rapid metabolism in the body, the changes in plasma concentration or effect compartment concentration of propofol were remarkably associated with sedation changes monitored by BIS [11,12]. Therefore, this study was carried out to measure BIS value at propofol discontinuation, time from propofol discontinuation to BIS ≥ 80, and propofol effect compartment concentration at BIS ≥ 80.…”
Section: Methodsmentioning
confidence: 99%